The Review of the Difference between Patients and Physicians in Terms of Severity Assessment and Therapeutic Goals in Androgenetic Alopecia in Japan - Yuya Harada; Shiro Niiyama; Hidetsugu Fukuda (Karger Publishers, 2021)
We often come across differences in the severity of androgenetic alopecia (AGA) as assessed subjectively by the patients themselves and objectively by the attending physicians. For the purpose of examining the differences in the assessment of AGA between patients and physicians, we presented the Norwood classification to male patients and the Shiseido classification to female patients and asked them to assess the degree of hair loss by themselves. We compared the results with the severity as assessed by 2 specified dermatologists. The results show that the assessments of the severity of AGA were consistent between the patients and physicians in 42% (15/36) of cases, the physicians reported a higher grade of severity than the patients themselves in 30% (11/36) of cases, and the patients reported a higher grade of severity than the physicians in 28% (10/36) of cases; however, the Wilcoxon signed rank statistical analysis showed no significant difference between the patients and physicians assessments. AGA should be treated in accordance with individual symptoms and wishes and not a standardized treatment protocol.